P212 Assessment of Crohn's disease activity using global MaRIA score in patients with ileal and ileocolonic disease. (27th May 2021) - Hrabric Sonje, K; Domislović, V; Brinar, M; Cukovic-Cavka, S; Turk, N; Grgic, D; Sjekavica, I; Krznaric, Z
Abstract: Background: Magnetic resonance index of activity (MaRIA) is composed of features independently associated with endoscopic disease activity and is surrogate marker of disease activity. The aim of this study was to evaluate correlation of global MaRIA (gMaRIA) with clinical and biochemical disease activity indices and diagnostic accuracy for active disease in patients with terminal ileum disease and ileocolonic disease. Methods: This is a cross-sectional study which included 251 patients with diagnosed CD. Global MaRIA (gMaRIA) index was calculated on 6 bowel segments (the distal ileum, ascending, transverse, descending, sigmoid colon and rectum) using following parameters: bowel wall thickness, ulcers, edema and relative contrast enhancement. Disease activity was defined as combination of clinical and biochemical disease activity (CRP>5 or HBI≥5). Disease extension was classified using Montreal classification (L1 ileum, L2 colon, L3 ileum and colon). Results: This study included 251 CD patients [age 35 (25–47), 55.3% males, BMI 21.8 (18–25) kg/m2, median disease duration 7 (2–15) years]. Ileal disease (L1) was present in 84 (33.5%) and ileocolonic disease (L3) in 151 (60.1%) patients. Correlation of gMARIA with biochemical indices of disease activity (CRP) was r=0.48, p<0.001 and with HBI r=0.33, p<0.001. Diagnostic accuracy of gMARIA in defining active disease in patients with L1 disease was considerably high [AUC 0.83 (95%CI 0.72–0.91)]. On the other hand, diagnostic accuracy in defining active disease in patients with L3 disease was good [AUC 0.71 (95%CI 0.62–0.79)], which is lower compared to L1 disease. In surgically naïve patients diagnostic accuracy of L1 disease was [AUC 0.88 (95%CI 0.72–0.96)], and for L3 disease [AUC 0.78 (95%CI 0.64–0.89)]. Conclusion: Global MaRIA index showed higher diagnostic accuracy in detecting clinically and biochemically active disease in terminal ileum compared to ileocolic disease. These results emphasize the important role of magnetic resonance enterography in monitoring disease activity in patients with isolated ileal disease. Global MaRIA score correlates better with biochemical disease activity compared to clinical disease activity, which points out to the significance of biochemical remission.